การจัดการเทคโนโลยีในฟาร์มสุกรเพื่อประสิทธิภาพระบบแก๊สชีวภาพ : รายงานฉบับสมบูรณ์ - ขันทอง สุนทราภา (จุฬาลงกรณ์มหาวิทยาลัย, 2009)
In the 1[subscript st] year, we have prepared several chitosan based membranes for separation of CO² from CH4 in biogas system. The molecular weight and degree of deacetylation of chitosan were 9.5x10⁵ dalton and 90±5%, respectively. Zeolite A having particle size, surface area and pore size of 2551.6 angstrom, 13.9 m² /g and 0.0137 c m³ /g was used. The studied types were crosslinked chitosan, uncrosslinked chitosan, crosslinked chitosan–zeolite, uncrosslinked chitosan–zeolite and swollen crosslinked chitosan–zeolite membranes. The crosslinking was done by immersing the membrane in 4% by weight of sulfuric acid solution. Zeolite A contents were varied in the range of 0–40% by weight of chitosan. The membranes were characterized for chemical structure, water uptake, morphology, tensile strength, gas permeability and gas pair selectivity. It was found that water uptake and gas pair selectivity increased with zeolite contents. However, tensile strength and gas permeability were decreased. It was found that the most potential type was 40% crosslinked chitosan–zeolite membrane. In testing dry gas with dry membrane at 30 ℃ and 1 bar, the permeability of CO², C H⁴, H² and N² were 66.8±6.4, 4.0±0.6, 387.5±26.1 and 7.4±0.6 barrers, respectively. The selectivity of CO²/ CH⁴, H²/CH⁴ and N²/ C H⁴ were 16.5±1.6, 96.9±1.5 and 1.9±0.1, respectively. These would be differed in testing non dry membrane and/or gas. Those results for swollen membrane and wet gas were 788.0±17.8, 20.6±2.2, 2102.1±31.8, 33.7±0.9 barrers, 38.2±0.2, 101.9±0.3 and 1.6±0.1, respectively. In onsite testing of crosslinked chitosan and 40% crosslinked chitosan–zeolite membranes at selected pig farm, it was found that 40% crosslinked chitosan–zeolite membranes showed better performance than the other corresponding to the ideal separation performance and corresponding to the ideal performance of dry membrane and dry gas.